2022
DOI: 10.1002/ldr.4253
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon stock assessment in forest ecosystems through pedogenic horizons and fixed depth layers sampling: What's the best one?

Abstract: In soil organic carbon (SOC) survey, the role of sampling approach is crucial and should not be underestimated. In this sense, the appropriateness of soil sampling by pedogenic horizons (PGH) and fixed depth layers (FDL) in forest is still a field of debate. The present work aimed to: (a) study the spatial variability of SOC concentrations and C stocks through PGH and FDL samplings in uneven-aged sweet chestnut, European beech and Norway spruce forests of the Apennine chain (Italy); (b) clarify the major advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 84 publications
1
4
0
Order By: Relevance
“…According to previous studies [22,123], within the study area, greater SOC and TN stocks were found at >1000 m a.s.l. compared to ≤1000 (Table 7).…”
Section: Organic C and Total N Stocks Within 0-30 Cm Soil Depthsupporting
confidence: 56%
See 4 more Smart Citations
“…According to previous studies [22,123], within the study area, greater SOC and TN stocks were found at >1000 m a.s.l. compared to ≤1000 (Table 7).…”
Section: Organic C and Total N Stocks Within 0-30 Cm Soil Depthsupporting
confidence: 56%
“…Specifically, sandstone weathering processes generate soils with low clay and base contents and a weak soil structure [61,67,89], making them vulnerable to erosion. With organic matter serving as the major actor for the formation and stabilization of soil aggregates [90,91], such vulnerability was further boosted by low clay content, which likely limited organic carbon retention within the mineral horizons [22,92,93] and led to thin A horizons (5.5 cm, on average). However, the incorporation of organic matter within the mineral horizons was likely further prevented by acidic conditions resulting in the accumulation of organic matter on the soil surface as organic horizons [94].…”
Section: Factors Affecting Pedodiversitymentioning
confidence: 99%
See 3 more Smart Citations